Incidence of CMV-HCV coinfection in renal transplant recipient. (3rd April 2012) - Chakraborty, Avirup; Patil, Krishna; Dasgupta, Sanjay; Tarafdar, Abhijit; Chakrabarti, Sekhar; Chakraborty, Nilanjan
Abstract : The authors report a case of a 47-year-old cytomegalovirus (CMV) immunoglobulin G (IgG) seropositive male patient with end stage renal disease who received a live renal transplant from a CMV IgG seropositive donor. Six months post-transplantation, the patient presented with reduced renal allograft function associated with fever, severe breathlessness, new onset jaundice and pancytopenia. His CMV DNA PCR came positive. Hepatitis C virus (HCV) RNA PCR also came positive (genotype I) though anti-HCV test performed before and after transplantation was negative. The patient was treated with oral valganciclovir and showed improvement of his clinical condition and was subsequently discharged under supervised therapy. However, the patient could not be treated for HCV because of risk of renal allograft rejection. The authors suggest oral valganciclovir for management of CMV infection and proper detection and eradication of HCV before renal transplantation to avoid future complications and prolongation of allograft survival.